International Institutions and Domestic Politics: Can Preferential Trading Agreements Help Leaders Promote Economic Reform?. (6th January 2014) - Baccini, Leonardo; Urpelainen, Johannes
Abstract : How do domestic politics influence the formation of international institutions, and how do international institutions shape domestic politics? These questions cannot be answered in isolation because national leaders form and join international institutions to advance their domestic interests. We illuminate the relationship between international institutions and domestic politics by analyzing whether preferential trading agreements (PTAs) promote liberal economic reform. In developing countries, leaders engage in PTA negotiations with major powers (European Union and United States) when these leaders want to implement reforms but cannot do so due to domestic political opposition and a lack of credible commitment. PTA negotiations promote economic reform by enabling credible commitment and allowing the leader to condition the implementation of the PTA on liberal policies.